EASTERN DNIEPER–DONETS DEPRESSION: PREDICTING AND DEVELOPING HYDROCARBON RESOURCES - Karpenko, O.; Mykhailov, V.; Karpenko, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Increasing geological exploration leads Ukraine’s priorities in oil and gas industry with a view to providing production gain in the proven hydrocarbon reserves. Unfortunately, a decrease in exploration drilling has reduced the resource base in the last ten years, ultimately reducing the number of the identified fields. Over the last 15-20 years there have been struck no prospective oil or gas deposits in Ukraine, with an exception of Kharkiv region, where test drilling revealed some in-place reserves at a depth of 1,900 – 4,300 m. In the future, prospective hydrocarbon reserves (of the same or bigger production potential) are likely to be discovered at greater depths, or when moving the vector of exploration drilling southward, towards an axial part of the basin. Considering the prospects of Donetsk region, prospective pools are likely to be found in the deposits of C1, C2 at depths of 4,000 – 5,000 m. The paper provides pessimistic, realistic and optimistic estimates of exploratory drill footage for oil and gas wells in Kharkiv and Donetsk areas. Predictive calculations of exploratory drilling in Kharkiv and Donetsk areas indicate high economic feasibility of a gradual increase in drill footage. It is caused by the presence of the resource base, discovery of the prospective pools, enhanced geophysical and drilling technologies, and recruitment of the investing companies. This will naturally multiply the number of the identified hydrocarbon deposits and increase the production gain in the proven reserves of oil and gas. Pessimistic estimates indicate an annual decline in exploration. Realistic estimates also suggest a reduction in the production gain in the proven reserves of hydrocarbons over time. The latter is determined by reconnaissance exploration of the deposits and hydrocarbon traps in Kharkiv region. Optimistic estimates are put down to introducing new high-performance exploration technologies in the short-term outlook, and to attracting investing companies. Much of the further production gain in Donetsk region is linked to the presence of tight gas bearing limestones, where natural gas may be obtained in large quantities by applying multistage fracturing.